Morphometric analysis of treatment effects of the Balters bionator in growing Class II patients - Antunes, Carina Ferlin; Bigliazzi, Renato [UNESP]; Bertoz, Francisco Antonio [UNESP]; Ortolani, Cristina Lúcia Feijó; Franchi, Lorenzo; Faltin Jr., Kurt (The Angle Orthodontist (EH Angle Education & Research Foundation), 2013)
Objective: To investigate the effects of the standard (Class II) Balters bionator in growing patients with Class II malocclusion with mandibular retrusion by using morphometrics (thin-plate spline [TPS] analysis). Materials and Methods: Thirty-one Class II patients (17 male and 14 female) were treated with the Balters bionator (bionator group). Mean age at the start of treatment (T0) was 10.3 years, while it was 13 years at the end of treatment (T1). Mean treatment time was 2 years and 2 months. The control group consisted of 22 subjects (14 male and 8 female) with untreated Class II malocclusion. Mean age at T0 was 10.2 years, while it was 12.2 years at T1. The observation period lasted 2 years on average. TPS analysis evaluated statistical (permutation tests) differences in the craniofacial shape and size between the bionator and control groups. Results: Through TPS analysis (deformation grids) the bionator group showed significant shape changes in the mandible that could be described as a mandibular forward and downward displacement. The control group showed no statistically significant differences in the correction of Class II malocclusion. Conclusions: Bionator appliance is able to induce significant mandibular shape changes that lead to the correction of Class II dentoskeletal disharmony. © 2013 by The EH Angle Education and Research Foundation, Inc.
Keywords: Class II malocclusion; Functional jaw orthopedics; Morphometric analysis; Thinplate spline analysis